Personal Authority Among Catholic Seminarians: Influence of Age and Ethnicity - Rovers, Martin W. (Canadian Journal of Counselling and Psychotherapy, 2007)
Personal authority is defined as the ability to balance individuation and intimacy in relationships with family and peers. Personal Authority in the Family System Questionnaire—College Version (PAFS-QVC) was completed by Catholic seminarians in Canada. Results of this research were compared to other studies of men. Seminarians were found to have more personal authority on most scales. Differences correlating to age and ethnicity were found. On the triangulation scale, scores were significantly correlated with age. On the peer individuation and peer intimacy scales, ethnic differences were found. A critic of PAFS-QVC is given. The implications for counselling are discussed.